ANALISIS MANAJEMEN PELAYANAN TERPADU SATU PINTU (PTSP) DALAM MENINGKATKAN KUALITAS PELAYANAN - Munirja Paputungan; Ni Made Ary Widyastini (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to describe (1) the supporting factors for implementing PTSP. (2) PTSP management system implementation and (3) PTSP management system in the Singaraja religious court. The method used in this research is descriptive qualitative. The data collection technique in this study was to conduct interviews with several informants including the head of the service sector, several service implementers and the community as PTSP service users. The results of this study indicate that: First, the supporting factors in the implementation of PTSP are facilities and infrastructure, there are innovations in supporting the running of PTSP. Second, the implementation of the PTSP management system at the Singaraja religious court is to achieve excellent service and simple and fast service. Third, the PTSP management system at the Singaraja religious court includes performance planning for the implementation of several actions that must be carried out, namely the front office that applies 5S (smile, greet, greet, polite, courteous) and services that are friendly to persons with disabilities such as providing tracking guides. performance development by conducting excellent service training where the activity is aimed at socializing the application of a culture of excellent service at the Singaraja Religious Court. Implementation of performance monitoring by looking at the absences of workers. Performance appraisal is carried out using a survey mechanism conducted on the community where the survey aims to measure the extent to which the service is carried out and is able to provide satisfaction to the community.